KAJIAN PRODUKTIVITAS TANGKAPAN BUBU KAWAT DENGAN KONSTRUKSI PERBEDAAN JUMLAH FUNNEL UNTUK NELAYAN SIBOLGA DENGAN ANALISIS MATEMATIKA - Juni Susanti Banurea; Marlina Wiguna Lumban Tobing (TAPIAN NAULI: Jurnal Penelitian Terapan Perikanan dan Kelautan, 2019)
Bubu is a trap that has one or two entrances operated at the base of the rocky waters. This wire mesh is known to fishermen as traps because the working principle of the trap is passive or waiting for the fish to enter. This tool is in the form of confinement like a closed room so that it won't be able to get out. The target fish of this trap fishing gear are reef fish or demersal fish.The purpose of this study was to determine the effect of the number of mouth openings (funnel) of wire traps on catches, determine the diversity of types of catches of wire traps and to find out the cost analysis of making wire traps. The research method used was experimental fishing with three units of wire mesh as a treatment each of three replications, namely the treatment of wire traps with two mouth openings (funnel) with three replications, treatment of wire trays with three mouth openings (funnel) with three replications and treatment of wire traps with four mouth openings (funnel) with three spaces. The hypothesis used in this study is H0: a hypothesis that illustrates that there is no significant effect on the difference in the number of wire mesh funnels on catches and H1: a hypothesis that describes a significant effect on the difference in the number of wire mesh funnels (funnel) the catch. Data obtained from the results of research in the form of the number of fish individuals were statistically tested using Analysis of Variants (ANOVA) with a completely randomized design (CRD) model.Based on the results of a study consisting of three treatments and three replications, the difference in the number of mouth traps (funnel) of wire traps proves that there is an influence on the catch when viewed from the number of fish caught. In accordance with the catches during the study, the highest number of catches was in the two mouth opening wire mesh trap (funnel) with an average of 5 catches per repetition. Furthermore, the catch of the three open mouth wire mesh traps (funnel) with an average number of catches of 3 tails per repetition and the lowest catches are in the four open mouth wire trap fishing gear (funnel) with an average number of results of 2 tails tank for each repetition . From the results of the number of fish caught by wire traps shows that F Count> F Table, the conclusion obtained from this study is that there is a significant influence on the amount of mouth opening (funnel) of wire traps on catches (Hypothesis H0 is rejected and Hypothesis H1 isaccepted).Keywords: Wire nets, mouth openings (funnel), catches